A revision of the Old World Black Nightshades (Morelloid clade of Solanum L., Solanaceae) - Särkinen, Tiina (2018)
The Morelloid clade, also known as the black nightshades or ?Maurella? (Morella), is one of the 10 major clades within Solanum L. The pantropical clade consists of 75 currently recognised non-spiny herbaceous and suffrutescent species with simple or branched hairs with or without glandular tips, with a centre of distribution in the tropical Andes. A secondary centre of diversity is found in Africa, where a set of mainly polyploid taxa occur. A yet smaller set of species is found in Australasia and Europe, including Solanum nigrum L., the type of the genus Solanum. Due to the large number of published synonyms, combined with complex morphological variation, our understanding of species limits and diversity in the Morelloid clade has remained poor despite detailed morphological studies carried out in conjunction with breeding experiments. Here we provide the first taxonomic overview since the 19th century of the entire group in the Old World, including Africa, Asia, Australia, Europe and islands of the Pacific. Complete synonymy, morphological descriptions, distribution maps and common names and uses are provided for all 19 species occurring outside the Americas (i.e. Africa, Asia, Australia, Europe and islands of the Pacific). We treat 12 species native to the Old World, as well as 7 taxa that are putatively introduced and/or invasive in the region. The current knowledge of the origin of the polyploid species is summarised. A key to all of the species occurring in the Old World is provided, together with line drawings and colour figures to aid identification both in herbaria and in the field. Preliminary conservation assessments are provided for all species.